Information interventions as a new dimension of Ukraine’s cyber-vulnerability - Diorditsa, Ihor V.; Telestakova, Armenui A.; Koval, Olga M.; Nazarenko, Olha A.; Nastiuk, Andrii A. (Linguistics and Culture Review, 2021)
In the article, the author analyzes information interventions as threats to the cybernetic security of Ukraine. The relevance of this study is due to the fact that large number of socially dangerous acts aimed at harming state interests can now be used both in the information space and in purely cyberspace. Since such actions are performed using computer systems and performed in cyberspace, we propose to define this type of intervention as “cybernetic intervention”, describing it as a separate group of socially dangerous acts aimed at damaging the information infrastructure of States, vital areas of society’s existence. The main aim of this study is to analyze information intervention as a threat to cyber security of Ukraine. The interpretation of terms that make up the conceptual and categorical apparatus of the subject of research is carried out. A narrow definition of the concept of “information intervention” is proposed as the violent intervention of one or more subjects of information relations in the activities of another or others, and a broad definition – a certain set of aggressive actions that are aimed at influencing public opinion and decision-making within one or another country and achieving clearly defined results.